التلصُّص الأنكلو- أمريكي وأعمال الكاتبات العربيات المترجمة - حرفوش, محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
In this paper, an attempt is being made to shed light on how frequently Anglo-American Arabists, translators, and commentators have dealt with translated Arab women's writings from a voyeuristic perspective, satisfying the Western reader’s negative and preconceived attitudes towards the Arab world. According to several specialists, one of the main objectives of translation is to manipulate literature in order to acquire a new function in the target-culture. This manipulation is examined with specific reference to a number of translated Arab women's writings. Besides, they have also been used to serve the prevalent Western feminist discourse on both the literary and ideological levels. All in all, they have given the Anglo-American literary circles a pretext to look down at the allegedly inferior Arab culture. يتضمّنُ هذا البحثُ محاولةً لإلقاء الضوء على كيفية قيام المستعربين، والمترجمين، والمعلقين الأنكلو-أمريكيين، بشكلٍ متواتر، بتناول أعمال الكاتبات العربيات المترجمة من منظور تلصّصي (فضولي)، يرضي مواقف القارئ الغربي المسبّقة والسلبية حيال العالم العربي. ويرى عددٌ من المختصين أنَّ أحد مرامي الترجمة يتجلّى في التلاعب بالأدب لكي يتّخذ وظيفةَ جديدة في ثقافة المستقر. كما يتمُّ رصد هذا التلاعب بالإحالة إلى حفنةٍ من أعمال الكاتبات العربيات المترجمة، التي تمّ استعمالها، علاوة على ذلك، لخدمة الخطاب الغربي النسوي السائد على صعيدي الأيديولوجيا والأدب. ومنحت [تلك الأعمال المترجمة]، على وجه الإجمال، الأوساطَ الأدبيةَ الأنكلو-أمريكية ذريعةً أخرى للنظر باستعلاء إلى الثقافة العربية الدونية افتراضاً.